Parental anxiety and depression are associated with adverse mental health in children with special needs during the COVID-19 pandemic - Gruszka, Piotr; Ganahl, Kristin; Stasch, Nicole; Burger, Christoph; Haberlandt, Edda; Bauer, Susanne M. (Frontiers in Public Health, 2023)
Introduction The coronavirus disease 2019 (COVID-19) pandemic has led to restrictions in various areas of life, including social life, work, leisure, health, and education. Vulnerable groups, such as children with special needs and their parents, may be at increased risk of experiencing exacerbated mental health problems during stressful periods such as the COVID-19 lockdowns. Materials and methods Telephone interviews were conducted with 954 parents of children with special needs. We assessed parental levels of generalized anxiety and depression using the validated GAD-7 and PHQ-8 scales. Parents were asked to rate family burden and their worry about the COVID-19 crisis, as well as their children's adverse mental health symptoms and health behaviors. Parents also reported their children's worries about the COVID-19 crisis. We conducted regressions to examine the relationship between parents' mental health problems and their children's adverse mental health symptoms and health behaviors. Qualitative data from open-ended questions were coded thematically and major themes of parental worry about the COVID-19 crisis were identified. Results Parental anxiety and depression symptoms predicted adverse mental health symptoms and behaviors in children with special needs. Criteria for current depression were met by 7.9% of parents of children with special needs, whereas 4.7% of the general population in Vorarlberg met the criteria for current depression according to data from the Austrian Health Interview Survey in 2019. Parental self-ratings of both depression and anxiety were highly correlated. The majority of parents reported being burdened (79.1%) or worried (67.8%) about the COVID-19 crisis. The main themes of parental worry about the COVID-19 crisis included COVID-19 infection (40.6%), economic situation (13.1%), uncertainty (8.4%), lack of social contact with family and friends (8.1%), family health status (7.5%), and school life (7.5%). Discussion Mental health symptoms in parents of children with special needs were strongly associated with increased adverse mental health symptoms and health behaviors in their children. Parents of children with special needs were more likely to be depressed during the COVID-19 pandemic than adults in 2019. We call for additional mental health support to reduce the mental health burden in families with children with special needs.